Obstetric care packages - Leyton Valencia, Imelda Beatriz (2019)
Maternal mortality and morbidity in the world remain a concern for maternal health care providers. The pathology associated with motherhood can be severe and even fatal, and is a major avoidable proportion. This motivates health teams to deploy efforts to improve safety in obstetrical care. In this context, initiatives to improve the quality of care are still vital to achieve this goal. Obstetric care packages are a series of measures to prevent or limit the severity of disease, and to facilitate the work of maternal care providers to obtain the best results.